Epicardial adipose tissue in patients with systemic sclerosis. (3rd October 2022) - Wang, X; Butcher, S; Myagmardorj, R; Liem, S; Vries-Bouwstra, J; Delgado, V; Bax, J; Marsan, N
Abstract: Background: Cardiac involvement is a major cause of death in patients with systemic sclerosis (SSc). Epicardial adipose tissue (EAT) has recently emerged as a mediator between systemic inflammatory disorders and cardiovascular disease, and may therefore play a role in the pathophysiology of cardiac involvement in SSc. Purpose: To assess the correlation between EAT mass and left ventricular (LV) function, and to determine the prognostic value of EAT in patients with SSc. Methods: Consecutive patients with SSc who underwent non-contrast thorax computed tomography and echocardiography were included. EAT mass was quantified using dedicated software (Figure A). The study endpoint was all-cause mortality. Results: A total of 230 SSc patients [age 53±15 years, 14% male] were included. The median value of EAT mass was 67g (IQR: 45–101g). Patients with increased EAT mass (≥67g) showed specifically more impaired LV diastolic function as compared to patients with less EAT mass (<67g). After adjusting for age and comorbidities, EAT remained independently associated with LV diastolic function parameters including left atrial volume index (B=0.031, P=0.025), LV mass index (B=0.139, P=0.036), E/E' (B=0.025, P<0.001) and E' (B=−0.012, P<0.001). During a median follow-up of 8 years 42 patients died, and by Kaplan-Meier analysis patients with increased EAT mass showed higher all-cause mortality rate as compared to patients with less EAT mass (log-rank p<0.001, Figure B). On multivariate analysis, EAT mass was independently associated with all-cause mortality (HR: 1.006; 95% CI: 1.001–1.010; p=0.010). Conclusion: In patients with SSc, EAT mass is independently associated with LV diastolic dysfunction and higher mortality rate. Funding Acknowledgement: Type of funding sources: None.